Genetic Profiling of the Causative Agents of Natural-Focal infections, Circulating in the Stavropol Territory - E. V. Chekrygina; A. S. Volynkina; E. S. Kotenev; Ya. V. Lisitskaya; O. A. Gnusareva; A. N. Kulichenko (Проблемы особо опасных инфекций, 2018)
Objective of the study was genetic typing of the strains and nucleic acid isolates of causative agents of natural focal infections, both bacterial and viral etiology, accumulation of data on genetic features of regional strains circulating in the Stavropol Territory. Material and methods. To study the genetic spectrum of causative agents of natural- focal infections, analysis of the strains and nucleic acids isolates detected in the samples of field and clinical material was carried out. Indication of causative agents of natural focal infections in the samples was carried out by PCR. For genetic typing of the strains and DNA/RNA isolates of natural focal infections agents, MLVA and sequencing of genome regions with subsequent phylogenetic analysis were used. The analysis of territorial distribution of the causative agent genetic variants and mapping was performed in ArcGIS 10.1. Results and conclusions. MLVA-25 typing of 20 strains of Francisella. tularensis, MLVA-10 typing of 4 Coxiella burnetii isolates, species identification of 20 isolates of Rickettsia sp., sub-species genetic typing of 40 RNA isolates of CCHF virus and 8 RNA isolates of hantaviruses circulating in the Stavropol Territory in 2016-2017 were performed. The studied strains of F. tularensis belong to eight MLVA genotypes. They are mainly confined to specific areas. The isolates of C. burnetii have the same MLVA type. Rickettsia, belonging to 5 species: R. massiliae R. raoultii, R. sibirica, R. aeschlimannii, R. slovaca, RNA-isolates of hantavirus of the «Tula» genotype and variants of the CCHF virus of the Europe-1 and Europe-3 genotypes were identified. The obtained data can be used in the epidemiological investigation of possible cases of infectious diseases to determine the source and pathways of infection.